Turing and Turing–Hopf Instabilities in Certain Kind of a Nonselfadjoint Reaction–Diffusion System - of, In this paper are being studied Turing; Turing–Hopf instabilities of solutions for reaction–diffusion systems under a certain type of nonselfadjoint boundary conditions. The root subspaces of the Laplace operator provided with such boundary conditions form a Riesz basis of subspaces; perturbations., that allows the standard procedure for the study of spatial or spatiotemporal pattern formation by considering the unstable Fourier normal modes of the linearized (Journal of Applied Nonlinear Dynamics, 2026)
In this paper are being studied Turing and Turing–Hopf instabilities of solutions for reaction–diffusion systems under a certain type of nonselfadjoint boundary conditions. The root subspaces of the Laplace operator provided with such boundary conditions form a Riesz basis of subspaces of L_2(Ω), that allows the standard procedure for the study of spatial or spatiotemporal pattern formation by considering the unstable Fourier normal modes of the linearized perturbations.